The Relationship Between Determinants of Shopping Sites and Customer E-Trust, Purchase Intention, Satisfaction, and Repurchase - Mehmet Emin Yaşar; Serhat Ata; Abdülvahap Baydaş (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The online purchasing status of consumers can be affected by many factors. One of these factors is website determinants. For consumers, online shopping involves more uncertainties than physical shopping. Especially in the current period, even daily basic needs are made with online shopping, which makes this situation even more difficult for both e-commerce businesses and customers. The aim of this study is to reveal the mediating role of customer e-trust in the relationship between determinants of shopping website and online purchase intention, satisfaction, and repurchase intention of customers. In this research, questionnaire method was applied on 321 participants and findings shows that image, interface, security, and privacy sub-dimensions of web determinants effect positively and meaningful purchase intention, customer satisfaction, and repurchase of customers. Besides, it was found that e-trust has partial mediating role in this relationship.